INFLUENCE OF FELLOW-EYE EXAMINATION INTERVAL ON VISUAL ACUITY AT FELLOW-EYE NEOVASCULARIZATION IN UNILATERAL TYPE 3 NEOVASCULARIZATION. Issue 7 (July 2020) - Kim, Jae Hui; Kim, Jong Woo; Kim, Chul Gu; Lee, Dong Won
Abstract : Purpose: To evaluate the influence of the fellow-eye examination interval on visual acuity at fellow-eye neovascularization in unilateral Type 3 neovascularization. Methods: This retrospective, observational study included 55 patients who were initially diagnosed with unilateral Type 3 neovascularization and subsequently developed fellow-eye neovascularization during the follow-up period. The fellow-eye examination interval was defined as the hospital visit interval between fellow-eye neovascularization detection and immediately before neovascularization detection. The primary outcome measures were the associations between the fellow-eye examination interval and fellow-eye best-corrected visual acuity (BCVA) at fellow-eye neovascularization detection and degree of deterioration in fellow-eye BCVA. Results: After the initial diagnosis of the first-involved eye, fellow-eye neovascularization was noted after a period of 22.7 ± 17.5 months. The mean fellow-eye examination interval was 4.8 ± 2.2 months (range, 2–10 months). The mean logarithm of the minimum angle of resolution BCVA in the fellow eye was 0.22 ± 0.18 (Snellen equivalents, 20/33) immediately before neovascularization and 0.52 ± 0.26 (20/66) at neovascularization. There were significant associations between the fellow-eye examination interval and fellow-eye BCVA when neovascularization was detected ( P = 0.005, r = 0.371) and at degree of deterioration in fellow-eye BCVA ( P = 0.001, r = 0.428). Conclusion: A longer fellow-eye examination interval was associated with poor visual acuity and greater visual deterioration of the fellow eye at neovascularization. These results suggest the need for frequent fellow-eye examination in patients with unilateral Type 3 neovascularization. Abstract : Longer fellow-eye examination intervals were associated with poor visual acuity and greater visual deterioration of the fellow eye at neovascularization. These results suggest the need for frequent fellow-eye monitoring in patients with unilateral Type 3 neovascularization.